Bioactivity guided cytotoxic activity of Clitoria ternatea utilizing brine shrimp lethality bioassay - Rahman, AKM Shahidur; Arslan, Oqna; Saha, Rama; Talukder, Nirupama; Khaleque, SMA; Ali, Husne Ara (Bangladesh Journal of Physiology and Pharmacology, 2009)
The crude methanol extract of leaves, seeds and stem-bark of Clitoria ternatea demonstrated a significant cytotoxic activity in a brine shrimp lethality bioassay test. The LC50 values of the crude methanol extract of leaves, seeds and stem-bark were found to be 25.82, 110.92, 179.89 μgm/ml respectively Among them crude methanol extract of leaves (25.82 μgm/ml) and methanol fraction of leaves (22.28 μgm/ml) showed a very promising cytotoxic activity. Further studies have been suggested to discover a novel bioactive compound from methanol fraction of leaves of Clitoria ternatea. DOI: 10.3329/bjpp.v22i1.3564 Bangladesh J Physiol Pharmacol 2006; 22(1/2) : 18-21